Building the Internet of Things. IN Microsoft Streamingsight. - Grabs, Torsten (MSDN magazine)
Emerging standards like HTML5 and Web sockets are enabling rich integration and control of devices and endpoints and laying the foundation for the Internet of Things. Learn how you can use your .NET skills at the device level to feed data into the powerful analytics capabilities of StreamInsight.